Narrative of Malaysian modernity COVID-19, Malay women portrayals and popular television serials - Syed, Md Azalanshah; Shamshudeen, Rosya Izyanie; Runnel, Christine; Abidin, Muhammad Zaiamri Zainal (2024)
Access online through this link: https://www.plarideljournal.org/article/narrative-of-malaysian-modernity-covid-19-malay-women-portrayals-and-popular-television-serials
Keywords: COVID-19 pandemic; Malays (Asian people); Popular culture; Women on television; Television series